Características clínicas y epidemiológicas de la endocarditis infecciosa en el Hospital Nacional Dos de Mayo, 2014-2019 - Ferrer Rodríguez, Carolina (2021)
Introduction. Infective Endocarditis (IE) is a disease caused by the invasion of pathogenic organisms into the cardiac endothelium. Objectives. To determine the clinical and epidemiological characteristics of Infectious Endocarditis in the Hospital Nacional Dos de Mayo, 2014-2019, Lima-Perú. Methods. Observational, descriptive and retrospective study. Patients older than 18 years with a diagnosis of IE according to modified Duke criteria, who had a complete blood count, blood culture, and echocardiogram were included. Results. 26 patients were studied; the average age was 46,96 ± 15,6 years, males predominated (57,7%), 15 came from Lima and 50% had completed secondary education as a degree. 57,7% (n = 15) had a negative blood culture, the most frequent symptoms were heart murmur (67,6%), fever (26%) and dyspnea (23,4%), the predominant complication was heart failure (61%). Comorbidities (47,1%) were the main risk factor. The mitral valve (51,7%) was the most compromised. The antibiotic regimen vancomycin + ceftriaxone and vancomycin + gentamicin, both with 19,2%, were the most used. 84,6% had erythrocyte distribution width (RDW) values > 14,4%. Of 10 who died, 9 had RDW > 14,4%. Conclusions. IE mainly affects males over 50 years of age with concomitant comorbidities. Positive echocardiography together with the Duke minor criteria were predominant. Most presented high RDW values that were related to the presence of complications and mortality, which was high.